Marketing support of putting on the own trade marks in the retail sector - Firsova S. (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article summarizes the practical experience of putting own trade mark by the domestic enterprise on the food market of Ukraine. The author has investigated the marketing strategy of putting on the own trade mark and evaluated its results for the enterprise, formed and implemented to the practice the measures for evaluating the attractiveness of company’s own trade mark.